Buenas prácticas de turismo sostenible para mejorar la gestión de los establecimientos de entretenimiento turísticos de la ciudad de Riobamba – Chimborazo - Erazo Salcedo, Laura Elizabeth (2018)
The present investigation it was realized by the neglect of the normative and regulations and low levels of social responsibility in the enterprise, the services that offer are of medium quality, the environments where the labor activities develop are not the optimum and the lack of a sustainable culture in the tourist industry, creating a dissatisfaction with the people who are acquiring a service that is not friendly with the nature and do not carry out with the wished expectations. Generating in this way stagnation in the tourist development of the city due to other cities believe a development and a competitive advantage on the tourist market of the country. The good sustainable practices are an essential tool during the process of business management inside the companies with the purpose of having an efficient service as well as internal and external client. Taking into account the advance that every day acquires the tourist activity in the Ecuador, carrying thousands of travelers with longing for knowing new places, which are capable of satisfying the own need of the tourist, the alternative exist of generating new tourist destinations, for that reason there is big efforts in order to develop the tourist activity, through of the implementation and adequacy of good practices of sustainable tourism, nevertheless there are problems related to the quality of products and tourist service, the socioeconomic performance, corporate development and the impact that generate them the tourist and daily activities in the environment.